2015
DOI: 10.1051/medsci/20153105010
|View full text |Cite
|
Sign up to set email alerts
|

La chémérine

Abstract: > La chémérine est une adipocytokine proinflammatoire exprimée et sécrétée majoritairement par les adipocytes. Elle a été initialement impliquée dans la régulation du système immunitaire, de l'adipogenèse et du métabo-lisme énergétique. Cependant, plusieurs études récentes montrent que cette adipocytokine et ses récepteurs sont exprimés au niveau des gonades. In vitro, elle diminue la stéroïdogenèse des cellules ovariennes et testiculaires de rongeurs et d'humains. La chémérine et ses récepteurs sont aussi pré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Chemerin is involved in the regulation of blood pressure, inflammation, immune responses, adipocytes differentiation, and carbohydrate metabolism and plays a key role in metabolic diseases, such as obesity and diabetes [ 202 ]. GPR1 knockout mice fed with a high-fat diet developed serious glucose intolerance and a test of pyruvic acid tolerance suppressed glucose-stimulated insulin levels that consequently increased glycaemia [ 203 ].…”
Section: Chemerinmentioning
confidence: 99%
“…Chemerin is involved in the regulation of blood pressure, inflammation, immune responses, adipocytes differentiation, and carbohydrate metabolism and plays a key role in metabolic diseases, such as obesity and diabetes [ 202 ]. GPR1 knockout mice fed with a high-fat diet developed serious glucose intolerance and a test of pyruvic acid tolerance suppressed glucose-stimulated insulin levels that consequently increased glycaemia [ 203 ].…”
Section: Chemerinmentioning
confidence: 99%
“…The region with the largest proportion of variance contains the RARRES2. Previous studies documented that RARRES2 regulates lipid metabolism and adipogenesis and mediates hormone secretion through gonadal functions in mice and humans (Goralski et al, 2007;Reverchon et al, 2015). Previous literature supported that the SNT occurrence may result from the abnormal secretion of hormone (Brka et al, 2002;Hotchkiss et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Lack of RARRES2 or CMLKR1 expression in vitro abrogates adipogenesis [1]. Recent studies showed that RARRES2 and CMKLR1 are expressed in the reproductive tract and could regulate gonadal functions [12]. Recombinant RARRES2 was found to suppress both basal estradiol secretion in granulosa cells (GC) from normal rats and FSH-induced progesterone and estradiol secretion in cultured preantral follicles and GC in vitro, suggesting the possible involvement of RARRES2 in the regulation of ovarian follicle growth and function [13, 14].…”
Section: Introductionmentioning
confidence: 99%